PENGARUH PEMBINAAN DINAS PEMBERDAYAAN MASYARAKAT KAMPUNG DAN PENGAWASAN INSPEKTORAT TERHADAP PENGELOLAAN PERTANGGUNGJAWABAN KEUANGAN PEMERINTAH DESA ATAS DANA DESA PADA PEMERINTAH DAERAH KABUPATEN LAMPUNG TENGAH - Vera Susanti; Syamsu Rizal; Indrayenti Indrayenti; Khairudin Khairudin; Haninun Haninun (Jurnal Akuntansi dan Keuangan, 2020)
Management of village government financial accountability for village funds is expected to be carried out transparently and accountably that it could give positive impacts on village financial management of village funds. The aspect of managing village financial accountability for village funds can be improved not only by conducting guidance for village officials and doing supervision by the inspectorate, but must be supported by other factors such as village officials who are competent enough in finance, system application that facilitate village financial managers or village apparatus, regulations that change rapidly in managing and reporting accountability, etc. The research subjects were 301 villages, with sample of 75 respondents. The results of the study were obtained DPMK guidance in a very good category.Supervision of the inspectorate in a very good category. Management of village government financial accountability for village funds in a very good category. DPMK guidance does not affect the village governments financial accountability for  village funds, Supervision of the inspectorate influences the financial management of village government for village funds, DPMK  guidance  and  Supervision  of  the  Inspectorate  influences  the  management  of village government financial accountability for village funds. DPMK guidance and Supervision of the Inspectorate together can improve village government financial management for village funds.